2021
DOI: 10.3390/brainsci11010058
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil-to-Lymphocyte, Platelet-to-Lymphocyte and Monocyte-to-Lymphocyte Ratio in Bipolar Disorder

Abstract: Background: Several inflammatory hypotheses have been suggested to explain the etiopathogenesis of bipolar disorder (BD) and its different phases. Neutrophil-to-lymphocyte (NLR), platelet-to-lymphocyte (PLR), and monocyte-to-lymphocyte (MLR) ratios have been proposed as potential peripheral biomarkers of mood episodes. Methods: We recruited 294 patients affected by BD, of which 143 were experiencing a (hypo)manic episode and 151 were in a depressive phase. A blood sample was drawn to perform a complete blood c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
31
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(38 citation statements)
references
References 49 publications
6
31
1
Order By: Relevance
“…First, PLR appeared significantly increased in (hypo)mania without any differences between males and females. This is in line with previous reports [40,41], in which PLR was uniquely associated with (hypo)mania. Since no gender difference was observed in PLR values while considering only the (hypo)manic subgroup of bipolar patients, it is possible to hypothesize that PLR may represent the strongest biomarker of (hypo)mania among the considered inflammatory ratios, regardless of gender.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…First, PLR appeared significantly increased in (hypo)mania without any differences between males and females. This is in line with previous reports [40,41], in which PLR was uniquely associated with (hypo)mania. Since no gender difference was observed in PLR values while considering only the (hypo)manic subgroup of bipolar patients, it is possible to hypothesize that PLR may represent the strongest biomarker of (hypo)mania among the considered inflammatory ratios, regardless of gender.…”
Section: Discussionsupporting
confidence: 93%
“…Our findings primarily confirm that several inflammatory ratios are consistently more elevated in (hypo)mania than MDE, further supporting the results of recent cross-sectional studies [39,40]. First, PLR appeared significantly increased in (hypo)mania without any differences between males and females.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Conversely, Inanli et al (2019) showed that only MLR is increased in manic episodes versus depression in BD [ 34 ]. On the other hand, a recent study observed that all ratios (NLR, MLR, and PLR) were increased in mania compared to bipolar depression but it is worth mentioning that the studied sample was not controlled for possible major confounders such as pathological conditions or treatment with anti-inflammatory drugs [ 63 ]. Our results are in agreement with those in the literature regarding NLR, MLR, and PLR between mania and bipolar depression.…”
Section: Discussionmentioning
confidence: 99%
“… 8 In bipolar disorder, the NLR, PLR, and LMR were significantly higher in (hypo)manic than depressed individuals. 9 …”
Section: Discussionmentioning
confidence: 99%